SMALL IS BEAUTIFUL: THE ROLE OF BOOK INDUSTRIES IN SMALL EUROPEAN COUNTRIES - KOVAČ, MIHA (Knygotyra, 2010)
This paper deals with four cultural and historical features of book industry that still determine the nature of book business. The paper concentrates on how these features impact book industries in linguistic communities with a relatively small number of speakers. The paper also examines the reasons for absence of the publishing education and contemporary publishing research in the world of academia. In its final part, the paper shows the reason why, at least for the time being, e-books will not outperform printed books and stresses that current developments have triggered not only new research on contemporary books, but also created a set of threats and opportunities for book business in small language communities.